PENGEMBANGAN PERANGKAT PEMBELAJARAN BARISAN DAN DERET MENGGUNAKAN METODE OUTDOOR LEARNING UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Theresia Siska Rikna Sari; Didik Sugeng Pambudi; Nurcholif Diah Sri Lestari (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Mathematical communication skills are important for students to have, but these abilities are still low. One reason is that the teacher's teaching method is still dominated by lectures in the classroom. This study aims to improve students' mathematical communication skills through the development of learning tools using the outdoor learning method on sequences and series material. Validation sheets, observation sheets, student response questionnaires and learning achievement tests are the data collected for analysis. The results of the validity of lesson plans, worksheets, and THB each reached a value of 4.6; 4.7; and 4.6 out of a maximum value of 5, which means it is valid. The results of the practicality analysis of the device reach 92%, which means it is practical. From the trial results, there were 80% of students in the active category, and positive student responses reached 84%. The minimum completeness of the learning outcomes test was obtained by 85.29% of the students in the experimental class, while the control class only reached 52.94%. From the results of the t-test it is evident that learning on sequences and series material with learning devices using outdoor learning methods has a significant effect on improving students' mathematical communication skills. Keywords: Mathematical Communication, Sequences and Sequences Material, Outdoor Learning Methods, Learning Devices.